Apparent energy, dry matter and amino acid digestibility of differently sourced soybean meal fed to Pacific white shrimp Litopenaeus vannamei. (31st October 2019) - Galkanda‐Arachchige, Harsha S. C.; Guo, Jingping; Stein, Hans H.; Allen Davis, Donald
Abstract: Due to the variations in nutrient quality of soybean meal (SBM) that is a result of differences in production location and processing specifications, a study was conducted to determine the fluctuations in apparent digestibility coefficients of differently sourced SBM fed to Pacific white shrimps ( Litopenaeus vannamei ). Twenty‐four SBM‐based diets were formulated by mixing a basal diet and test ingredients on a dry matter basis (70:30 ratio), while 1% chromic oxide was used as the inert marker. The digestibility trial was carried out in a semi‐closed recirculation system with six replicate groups per treatment (mean shrimp weight of 10.2 g). Significant differences were observed for apparent dry matter, energy and protein digestibility coefficients ( p < .05 was considered significant) among 24 sources of SBM and digestibility values ranged from 45% to 90%, 56% to 93% and 87% to 98%, respectively. Based on multivariate analysis, acid detergent fibre, neutral detergent fibre, lignin, raffinose and trypsin inhibitor were screened as the key chemical characteristics in SBM that influenced digestibility of nutrients in Pacific white shrimps. Variations in growth performances of shrimp were in line with the variations in apparent digestibility coefficients of SBM verifying the importance of digestibility data in shrimp feed formulations.